James Parry interviewed by John Bannister in the Perth Independent Music project - Parry, James, 1963-; Bannister, John (William John Egerton), 1967- (2008)
James Parry talks about his career as a singer of the Marigolds; his musical influences; the Perth music scene in the 1970s, 80s and 90s; forming of the band; rehearsals; song writing; touring in WA and the East Coast of Australia; reviews in Australia and overseas; the bands they influenced; finances; Triple J; the current music scene of Perth.
Recorded on April 16, 2008 in Perth, W.A.
Digital master available
Timed summary (7 p.) and uncorrected transcript (typescript, 65 leaves) available.
Keywords: Parry, James, -- 1963- -- Interviews; Marigolds (Musical group) -- Anecdotes; Marigolds (Musical group) -- History; Singers -- Western Australia -- Interviews; Musicians -- Western Australia -- Interviews; Music -- Western Australia -- 20th century -- History; Music -- Australia -- 20th century -- History; Singers; Musicians